Seedling Quality in Brutian Pine (Pinus brutia Ten.) - Nebi BİLİR (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2019)
This study carried out on Brutian Pine (Pinus brutia Ten.) which had the largest natural distribution in Turkey to contribute nursery practices, plantation, and genetic-breeding of the species. Seedling height and root-collar diameter were examined in 1+0 bareroot and 1+1 years containerized seedlings grown from a seed stand at Antalya Forest Nursery at the end of growing period of 2018. Seedling quality and relation between the characteristics were investigated on seedlings sampled from 200 seedlings each age group.